Personal relevance and state empathy with a character facilitates self-disclosure in film viewers - Bálint, Katalin; Sukalla, Freya; Rooney, Brendan (Frontiers in Communication, 2022)
Eudaimonic media entertainment has been shown to promote mental health, however, our knowledge of the underlying mechanisms that drive the effect is still limited. This project focuses on self-disclosure, a relevant factor for reducing distress and improving mental well-being. The aim was to test whether empathizing with a fictional character and the personal relevance of a story can facilitate self-disclosure responses, as well as to examine the role of social cues and audio-visual formal features. In Study 1, 227 participants were randomly assigned to watch one of 8 videos of individuals sharing their experiences of burnout. Shot scale and social cues were manipulated in the videos. Empathy with the characters but not personal relevance predicted the desire for self-disclosure. In Study 2, participants were randomly assigned to either a control condition (n = 78) or one of six manipulated short films (n = 436). Movies were manipulated for shot scale and music. Participants’ reports on state empathy with the film character, perceived personal relevance of the story, and measures related to self-disclosure were collected. One week later, participants were invited to a second survey on self-disclosure behavior (n = 390). Both personal relevance and empathy with character showed strong links to self-disclosure responses. The findings of this project shed light on how self-disclosure is elicited by narratives. These insights are important to further understand the therapeutic effects of narratives.